Unity and diversity in microbial genomes - Sakharkar, Kishore (Henry Stewart Talks, 2007)
Host-pathogen interaction, Microbial genomics, Properties and functions of microbes: their genomes, protein coding, sequences and putative biochemical pathways, The concept of the "universal" minimal genome, Strategies used by obligatory intracellular parasites for genome reduction and survival, The use of comparative genomics in understanding the concept of the "backbone genome", Differential gene loss and overlapping genes, Drug targets
Archived at 2018/05/31